2011
DOI: 10.1097/igc.0b013e3182157a19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk Factors for 30-Day Hospital Readmission After Surgical Cytoreduction in Epithelial Ovarian Carcinoma

Abstract: The most common reason for readmission after cytoreductive surgery for EOC is small bowel obstruction/ileus. Studies assessing postoperative disease management programs including nursing telephone follow-up, administration of outpatient intravenous fluids, and continuation of antithrombotic agents may offer opportunities to reduce readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…[13][14][15] Recently, studies focusing on readmission rates in patients undergoing laparoscopic cholecystectomy, surgical cytoreduction of epithelial ovarian carcinoma, lung transplantation, and small bowel obstruction surgery have been reported. [16][17][18][19] Various programs for postoperative management have been proposed to reduce the likelihood of readmission. 17 Similarly, readmission is considered prevalent and costly in medicare fee-for-service programs in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Recently, studies focusing on readmission rates in patients undergoing laparoscopic cholecystectomy, surgical cytoreduction of epithelial ovarian carcinoma, lung transplantation, and small bowel obstruction surgery have been reported. [16][17][18][19] Various programs for postoperative management have been proposed to reduce the likelihood of readmission. 17 Similarly, readmission is considered prevalent and costly in medicare fee-for-service programs in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Various programs for postoperative management have been proposed to reduce the likelihood of readmission. 17 Similarly, readmission is considered prevalent and costly in medicare fee-for-service programs in the United States. According to the Medicare Payment Advisory Commission report, as much as US$12 billion is spent on potentially avoidable hospital readmissions each year.…”
Section: Discussionmentioning
confidence: 99%
“…9,12Y14 In this study, the rate of rehospitalization was identified to be 48.0% within 90 days of discharge. In a study conducted on patients with gynecological cancer by Henretta et al, 15 the population of the study was 324 women with gynecological cancer, and the rate of rehospitalization was 13.2%; in the study of Fauci et al, 16 the population for the study was 207 women with ovarian cancer who underwent surgery, and the rate of rehospitalization was 16.0%. In the study conducted by Alhilli et al, 17 where the patient population was 324 women who have epithelial ovarian cancer, the rate of rehospitalization was 19.3%.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the most common perioperative complications were cardiopulmonary events and small bowel obstruction. Fauci et al (26) found that comorbidity was highly associated with readmission within 30 days of discharge, and small bowel obstruction/ileus was the most common reason for this entity. Cai et al (27) also reported the major complication rate as 22% in their debulking surgery series.…”
Section: Discussionmentioning
confidence: 99%